Pengaruh Motivasi dan Literasi Keuangan Terhadap Minat Berinvestasi di Pasar Modal - Shafrani, Yoiz Shafwa (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2017)
Economic development requires everyone to be able to manage their financial assets. Financial Services Authority (OJK) survey results found that the lower social strata of society is, the lower the level of literacy will be. Based on these facts, the OJK, together with the Financial Services Industry (IJK), continues to encourage and implement literacy programs and financial inclusion so that the target of financial inclusion index can be achieved. One of the targetgroups of the program is academics, both in primary and secondary education and in universities. In 2016, Indonesia Stock Exchange (IDX) Yogyakarta Branch seeks to increase public investment in the capital market through financial literacy program. This program is conducted in cooperation with OJK and several Capital Investment Companies through the procurement of socialization at several universities in Central Java and Yogyakarta. The activity was followed up by OJK Purwokerto through a program called Gebyar Syariah, which was intended to increase Banyumas community investment interest. At the event, Banyumas regency won two records from the World Record Museum of Indonesia or MURI. The record is the Creation of Shariah Fund Investors Category of Public Society of 5,546 people and the highest Shariah Investor Generation of 2.000 people. The university that obtained the MURI record is Muhamdiyah University of Purwokerto. Regression Analysis with hypothesis testing using t test and F test.The result when connected with the results of F test found that thevariables of financial literacy and motivation simultaneously influence the investment interest. Meanwhile, when viewed from test result, it was found that each independent variable (variable of motivation and financial literacy) influence to dependent variable, that is variable of interest to invest The purpose of this research is to know whether there is influence of financial literacy and motivation to investment interest in capital market. The method of analysis used in this study is Multiple Linear Regression Analysis with hypothesis testing using t test and F test. The result when connected with the results of F test found that thevariables of financial literacy and motivation simultaneously influence the investment interest. Meanwhile, when viewed from t test result, it was found that each independent variable (variable of motivation and financial literacy) influence to dependent variable, that is variable of interest to invest.